Prevention of adverse events during intra-hospital transport: an integrative review (Research, Society and Development, 2022)
Objective: To identify available evidence on care for the prevention of adverse events during intra-hospital transport of critically ill adult patients. Method: Integrative review of scientific articles published in the last 10 years on databases of the Virtual Health Library; Medical Literature Analysis and Retrieval System Online; Scopus and Web of Science that answered the following question: What precautions should be taken to prevent adverse events during intra-hospital transport of critically ill adult patients? The selection of studies was performed by two reviewers independently. Data extraction was performed using a standardized instrument. Results: Nine out of the 640 studies identified were included in this review. In the selected studies, we observed that intra-hospital transport brings risks to critical patients. The implementation of protocols and the use of checklists were the most frequent strategies used to prevent adverse events during intra-hospital transport of critically ill adult patients. Efficient communication and definition of the transport team were also strategies presented and discussed in the studies. Conclusion: The use of protocols and checklists in hospital routine is an important tool for the prevention of adverse events resulting from intra-hospital transport.